Bring your own devices (BYOD) survival guide - Keyes, Jessica, 1950- (Boca Raton, Fla. : Taylor & Francis, 2013)
"This book explains and then helps readers live with the psycho-techno phenomenon that is bring your own technology (BYOT). Readers will learn how to understand these new end-users and their demands, as well as the strategic and tactical ramifications of these demands. Next, it covers the broad range of technical considerations such as selection, connectivity, training, support, and security. The text includes best practices and case studies of well-known companies, including IBM, Ford, and CarFax"--
"An Auerbach book."
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer technical support; Electronic books